Impact of Internet use on the World of Education - Anita Candra Dewi; Kurniawan; Rahmat Hidayat; Siti Mufliyani Mutmainnah; Syamsinar; Nurlatifah Amir (MultiTech Publisher, 2023)
Information technology is developing rapidly and surpassing industry which has an impact on all aspects, one of which is the field of education. One form of implementation of technological developments is the use of the internet in the educational sector. The internet is a phenomenon in the world of education, by using the internet it is easy to obtain various educational sources, accessing information 24 hours a day without holidays whenever they exist. Therefore, the aim is to find out the impact of the internet on education, the role of the internet in the world of education, and how to respond to the impact of the internet on the world of education. Which produces or describes positive, negative impacts, influences, and how to respond to internet use in the world of education.